2021
DOI: 10.22270/jddt.v11i6.5080
|View full text |Cite
|
Sign up to set email alerts
|

Acute and subacute toxicity assessment of an aqueous extract of Crotalaria retusa (Fabaceae) in Swiss mice and Wistar rats

Abstract: The present study is a contribution to the enhancement of Ivorian traditional medicine, by carrying out bio-tolerance tests of an aqueous extract of the aerial parts of Crotalaria retusa (EACr) in mice and rats according to the guidelines of the Organization for Economic Co-operation and Development (OECD) 423 and 407, respectively. The doses of 2000 and 5000 mg/kg of body weight (BW) of the extract were used for acute toxicity. For subacute toxicity which lasted 28 days, doses of 500, 1000, and 2000 mg/kg BW … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…These results are similar to those obtained with many medicinal plants in the African pharmacopoeia, such as Crotalaria retusa L (Fabaceae) [9], Parkia biglobosa (Mimosaceae), [10] Annona senegalensis (Annonaceae) and Hallea senegalensis (Rubiacaceae) [11].…”
Section: Discussionsupporting
confidence: 86%
“…These results are similar to those obtained with many medicinal plants in the African pharmacopoeia, such as Crotalaria retusa L (Fabaceae) [9], Parkia biglobosa (Mimosaceae), [10] Annona senegalensis (Annonaceae) and Hallea senegalensis (Rubiacaceae) [11].…”
Section: Discussionsupporting
confidence: 86%
“…According to the OECD globally harmonised classification system, the aqueous leaves extract of Ceiba pentandra and its fraction can be classified in category 5 and considered to be non-toxic by the oral route. This absence of toxicity by gavage is also observed with other plant extracts from the traditional African pharmacopoeia, such as the aqueous of fresh leaves extract of Cymbopogon citratus (Poaceae) [9] , the acetic extract of Morinda morindoides (Rubiaceae) [10] and the aqueous extract of the whole plant of Crotalaria retusa (Fabaceae) [11] . These authors have shown that these different extracts have LD50 values greater than 5000 mg/kg B.W.…”
Section: Discussionmentioning
confidence: 54%
“…Similarly, no significant change was observed in the weight of the investigated organs (liver, lungs, kidneys and heart), suggesting that the daily administration of our extract for 28 days at doses studied, had no effect on their normal growth. The relative weight of the organs is considered to be a relatively sensitive indicator in the toxicity study [20].…”
Section: Discussionmentioning
confidence: 99%